Pemberdayaan Zakat Produktif dengan Corak Kampung Zakat - Emi Yasir (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2023)
Productive zakat is currently a growing trend among the people of Aceh. Zakat is also a social activity that can be a solution to the current poverty. Previous studies in several places regarding productive zakat empowerment were still not optimal due to several obstacles that had to be addressed. This study aims to determine the implementation and implementation of productive zakat empowerment with the village zakat model in Aceh Besar District. This research uses a qualitative approach with descriptive methods. The data was collected by interviewing using purposive sampling technique. Samples taken are Mustahiq, Baitul Mal Institute, and Islamic Sharia Service. The empowerment of productive zakat is measured using three indicators of zakat distribution, village feasibility, and business results from productive zakat. Based on the results of this study, productive zakat with the village-based zakat model is a positive activity that can lead to an independent attitude for the community in managing businesses and improving the welfare of the less fortunate and increasing their standard of living.Keywords: Productive Zakat; Zakat Village; Zakat Empowerment AbstrakZakat produktif saat ini menjadi sebuah tren yang berkembang pesat di kalangan masyarakat Aceh. Zakat juga merupakan suatu kegiatan sosial yang dapat memeberikan solusi terhadap kemiskinan yang melanda saat ini. Kajian terdahulu dibeberapa tempat dalam pemberdayaan zakat produktif masih belum optimal disebabkan beberapa kendala yang harus dibenahi. Penelitian ini bertujuan untuk mengetahui pelaksanaan dan potensi pemberdayaan zakat produktif dengan corak Kampung zakat di Kabupaten Aceh Besar. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Pengumpulan data dilakukan dengan cara wawancara yang diambil menggunakan teknik purposive sampling. sampel yang diambil merupakan mustahiq, lembaga baitul mal, dan dinas syariat Islam. Pemberdayaan zakat produktif diukur menggunakan tiga indikator distribusi zakat, kelayakan kampung, hasil usaha dari zakat produktif. Hasil penelitian menunjukan bahwa zakat produktif dengan corak kampung zakat merupakan kegiatan positif yang dapat membentuk sikap kemandirian bagi masyarakat dalam mengelola usaha dan meningkatkan kesejahteraan serta meningkatkan taraf kehidupan dalam menjalani keberlangsungan hidup.Kata Kunci: Zakat Produktif; Kampung Zakat; Pemberdayaan Zakat